No todo lo que brilla es oro - Rabinovich, Daniel (Pontificia Universidad Católica del Perú, 2022)
This philatelic corner is a tribute to pyrite, a brilliant mineral with attractive geometric shapes that has always excited collectors and geologists worldwide and whose relevance has been captured on the stamps of many countries.

Este rincón filatélico es un homenaje a la pirita, un mineral brillante con formas geométricas caprichosas que ha entusiasmado siempre a coleccionistas y geólogos de todo el mundo, y cuya relevancia ha sido plasmada en las estampillas de numerosos países.
Not all that glitters is gold
Keywords: Pyrite; Stamps; Pirita; Estampillas; https://purl.org/pe-repo/ocde/ford#1.04.00